PENGARUH KONSELING KELOMPOK DENGAN TEKNIK MINDFULNESS DALAM MENGURANGI BURNOUT AKADEMIK PADA MAHASANTRI SEMESTER AKHIR DI PONDOK PESANTREN AL-QUR’AN IBNU KATSIR 1 JEMBER - Madhani, Miftah Ismatullah; Nasruliyah Hikmatul Maghfiroh; Imaratul Ulwiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of group counseling using mindfulness techniques in reducing academic burnout among final-year students at Pondok Pesantren Al-Qur’an Ibnu Katsir 1 Jember. Purposive sampling was used to select the research sample. This study employed a quantitative method with a pre-experimental design using One Group Pre-Test Post-Test. Data analysis was conducted using the Wilcoxon test with SPSS version 25.0. The Wilcoxon test results showed a Z value of -1.826 with a two-tailed Asymp. Sig of 0.068. Since the Asymp. Sig (2-tailed) > 0.05, it can be concluded that Ha is accepted, indicating that group counseling with mindfulness techniques effectively reduces academic burnout among final-year students at Pondok Pesantren Al-Qur’an Ibnu Katsir 1 Jember.